Swimming with the shoal - Childs, A (Springer Nature, 2017)
This article responds to Yuli Rahmawati and Peter Charles Taylor’s piece and explores my role as a science teacher, science teacher educator and researcher in two contexts, Sierra Leone and Bhutan. In the first part of the article I reflect on my 3 years as a science teacher in Sierra Leone and demonstrate resonances with Yuli’s accounts of culture shock and with her positioning of herself in a third space. I also reflect on the importance of colleagues in helping me reshape my identity as a science teacher in this new context. The second part of the article reflects on much shorter periods of time in Bhutan and my work as a teacher educator and researcher where, unlike Sierra Leone, it was not possible because of the short periods I worked there, to occupy a third space. I close by discussing how in Bhutan, but also Sierra Leone, collaboration with colleagues allowed me to contribute my own expertise, despite my lack of a deep understanding of the cultural context, in a way that was as valuable as possible. I liken this way of collaborative working in my professional life as ‘swimming with the shoal’.